Lithuanian material in the Sound Archive in Berlin and Adalbert Bezzenberger’s work in Lithuanian studies during the First World War - Kiseliūnaitė, Dalia (Baltistica, 2021)
The article discusses the Lithuanian materials in the Sound Archive (Lautarchiv) of the Humboldt University of Berlin that are still unknown to the Lithuanian science. These include speech and music audio recordings made in World War I prisoner-of-war camps. The collection of recordings was organized by the Royal Prussian Phonographic Commission (Königlich Preußische Phonographische Kommission), and the language data collection was supervised by W. Doegen. The publication focuses on the contribution of the famous expert of the Baltic languages A. Bezzenberger in selecting respondents according to their ability to represent the native dialect. The study of the completed questionnaires and audio recordings reveals that the researcher knew the features of Lithuanian dialects and the methodological principles of dialect data collection and understood the importance of new technologies - sound recording and reproduction - for linguistics. The article also presents the historical and scientific context of the project itself. It emphasizes the value of the surviving sound recordings for the history of documentation and study of Lithuanian dialects. Although the recordings made during World War I are not flawless technically, they can be used for comparative dialectological research and investigation of the development of separate Lithuanian dialects, as well as other geolinguistic studies.
Keywords: history of Lithuanian phonography; history of dialectology; language documentation; World War I; Wilhelm Doegen; Adalbert Bezzenberger